Charge-conversional zwitterionic copolymer as pH-sensitive shielding system for effective tumor treatment. (15th October 2015) - Chen, Jie; Dong, Xuan; Feng, Tianshi; Lin, Lin; Guo, Zhaopei; Xia, Jialiang; Tian, Huayu; Chen, Xuesi
Graphical abstract: Abstract: A novel pH-responsive gene delivery system for tumor acidity-targeted p DNA delivery is prepared by introducing a rapid charge-conversional zwitterionic copolymer to the positive surface of PEI/ p DNA complexes through electrostatic interaction. The shielding system (OEAL) consists of oligoethylenimine (OEI), poly(l -aspartate) (PBLA), and poly(l -lysine) (PLL). The charge-conversional behavior of the OEAL/PEI/DNA ternary complex is evaluated by zeta potential assay. The surface charges of the complexes can change from negative to positive in the pH range of 7.4–6.8. Under a simulative in vivo environment, OEAL/PEI/DNA exhibits promotion of cellular uptake by tumor cells and enhanced gene transfection efficiency because of its good charge-conversional properties. Antitumor experiments further show that the pH-responsive charge-conversional system can mediate a therapeutic gene that can induce tumor apoptosis ( p KH3-rev-casp-3) to achieve effective tumor inhibition. Accordingly, OEAL can be regarded as a promising tumor microenvironment-sensitive gene delivery shielding system for antitumor therapy. Statement of Significance: This manuscript focused on the novel pH-responsive gene delivery system for tumor acidity-targeted p DNA delivery. The novel system is prepared by introducing a rapid charge-conversional zwitterionic copolymer, consisting of oligoethylenimine, poly(l -aspartate) and poly(l -lysine), to the positive surface of PEI/ p DNA complexes. The surface charges of the complexes can change from negative to positive from pH 7.4 to 6.8. OEAL/PEI/DNA shows promoting cellular uptake by tumor cells and enhanced gene transfection efficiency. The antitumor experiments further show that the pH responsive charge conversional system can mediate p KH3-rev-casp-3 to achieve effective tumor inhibition. Accordingly, OEAL can be regarded as a promising tumor microenvironment sensitive gene delivery shielding system for antitumor therapy.